Fabrication and performance evaluation of waste cotton and polyester fiber‐reinforced green composites for building and construction applications. Issue 6 (22nd March 2021) - Kamble, Zunjarrao; Behera, Bijoya Kumar
Abstract: This research reports thermoset composites reinforced with cotton and polyester fibers (recovered from pre‐consumer textile waste). The carded web of cotton and polyester fibers and epoxy resin were used to develop the composites using the compression molding technique. The polyester/epoxy composites show average tensile and impact strength higher than cotton/epoxy composites. However, cotton/epoxy composites show average flexural strength higher than polyester/epoxy composites. The bearing strength in a pinned joint for polyester/epoxy composites is higher than cotton/epoxy composites. The equilibrium water content of polyester/epoxy composites was found much less than the corresponding cotton/epoxy composite. The cotton/epoxy and polyester/epoxy composites are thermally stable enough. Abstract : Development of thermoset composites using waste cotton and polyester fibres. Effect of fibre volume fraction on the mechanical properties of cotton/epoxy and polyester/epoxy composites. Effect of water absorption on mechanical properties of cotton/epoxy and polyester/epoxy composites. Effect of composite thickness on mechanical properties of cotton/epoxy composites. Water absorption and thermogravimetric properties of cotton/epoxy and polyester/epoxy composites.